2014
DOI: 10.1177/1077558714533826
|View full text |Cite
|
Sign up to set email alerts
|

Why and How Six Aligning Forces for Quality Communities Have Focused on Reducing Disparities

Abstract: Public reports on provider performance can help guide consumers' health care decisions, yet consumer awareness and use of public reports is low and may be even lower among racial/ethnic minorities. In this qualitative research article, we describe activities implemented by multi-stakeholder alliances in six U.S. communities to increase minorities' awareness of public reports. We also describe alliances' motivation for deliberately targeting greater awareness among minorities. We found that alliances' decision … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Prior research found that African American survey respondents were less likely than white survey respondents to report seeing comparative quality information for hospitals and doctors [28], even though once minorities are aware of reports, they are more likely to use the information [28,29]. To the degree that use of quality information drives health outcomes, disseminating the information to vulnerable populations, as some communities are already trying to do [30], is one approach to avoid widening existing disparities. Additional research is needed regarding whether vulnerable populations have a choice of provider and, if so, the most effective way to disseminate and encourage the use of the quality information to this group [11].…”
Section: Discussionmentioning
confidence: 99%
“…Prior research found that African American survey respondents were less likely than white survey respondents to report seeing comparative quality information for hospitals and doctors [28], even though once minorities are aware of reports, they are more likely to use the information [28,29]. To the degree that use of quality information drives health outcomes, disseminating the information to vulnerable populations, as some communities are already trying to do [30], is one approach to avoid widening existing disparities. Additional research is needed regarding whether vulnerable populations have a choice of provider and, if so, the most effective way to disseminate and encourage the use of the quality information to this group [11].…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of the primary study was that participants had higher education levels than the median norm for Chicago (Yonek & Hasnain-Wynia, 2011). Thus, findings may not represent all African American women in Chicago.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we had an overrepresentation of low-income and racial minorities in our sample compared to the expected population. However, our sample represents a high-priority population as a proposed strategy to reduce health disparities and improve health outcomes by making health information, such as public reports available to racial and ethnic minorities [39]. …”
Section: Discussionmentioning
confidence: 99%